Effect of a general practitioner management plan on health outcomes and hospitalisations in older patients with diabetes. Issue 12 (December 2016) - Caughey, G. E.; Vitry, A. I.; Ramsay, E. N.; Gilbert, A. L.; Shakib, S.; Ryan, P.; Esterman, A.; McDermott, R. A.; Roughead, E. E.
Abstract : Background: Little is known about the impact of a general practitioner management plan (GPMP) on health outcomes of patients with diabetes. Aim: To examine the impact of a GPMP on the risk of hospitalisation for diabetes. Methods: A retrospective study using administrative data from the Australian Government Department of Veterans' Affairs was conducted (1 July 2006 to 30 June 2014) of diabetes patients either exposed or unexposed to a GPMP. The primary end‐point was the risk of first hospitalisation for a diabetes‐related complication and was assessed using Cox proportional hazard regression models with death as a competing risk. Secondary end‐points included rates of receiving guideline care for diabetes, with differences assessed using Poisson regression analyses. Results: A total of 16 214 patients with diabetes were included; 8091 had a GPMP, and 8123 did not. After 1 year, 545 (6.7%) patients with a GPMP and 634 (7.8%) of patients without a GPMP were hospitalised for a diabetes complication. There was a 22% reduction in the risk of being hospitalised for a diabetes complication (adjusted hazard ratio (HR) 0.78, 95% confidence interval (CI) 0.69–0.87, P < 0.0001) for those who received a GPMP by comparison to those who did not. Increased rates of diabetes guideline care, HbA1c claims (adjusted HR 1.29, 95% CI 1.25–1.33) and microalbuminura claims (adjusted HR 1.65, 95% CI 1.58–1.72) were observed after a GPMP. Conclusion: Provision of a GPMP in older patients with diabetes resulted in improved health outcomes, delaying the risk of hospitalisation at 12 months for diabetes complications. GPMP should be included as part of routine primary care for older patients with diabetes.